Screening of global microbiomes implies ecological boundaries impacting the distribution and dissemination of clinically relevant antimicrobial resistance genes - Qiang Lin; Basil Britto Xavier; Blaise T. F. Alako; Alex L. Mitchell; Sahaya Glingston Rajakani; Youri Glupczynski; Robert D. Finn; Guy Cochrane; Surbhi Malhotra-Kumar (Communications Biology, 2022)
An extensive metagenomic analysis investigates the global distribution of antimicrobial resistance genes over different biomes, which are primarily influenced by host genera and environment rather than geographic or anthropogenic factors.